Effect of NETs/COX-2 pathway on immune microenvironment and metastasis in gastric cancer - Zhang, Ange; Zou, Xiaoming; Yang, Shifeng; Yang, Hao; Ma, Zhen; Li, Jiacheng (Frontiers in Immunology, 2023)
Neutrophil extracellular traps (NETs) are crucial in the progression of several cancers. The formation of NETs is closely related to reactive oxygen species (ROS), and the granule proteins involved in nucleosome depolymerization under the action of ROS together with the loosened DNA compose the basic structure of NETs. This study aims to investigate the specific mechanisms of NETs promoting gastric cancer metastasis in order to perfect the existing immunotherapy strategies. In addition, bioinformatics predictions revealed the essential role of COX-2 in the tumor microenvironment (TME) of GC and the significant correlation between COX-2 and immunotherapy. The clinical sample detection showed the expression of NETs and cyclooxygenase-2 (COX-2) was considerably increased in tumor tissues. In vitro experiments, our studies demonstrated that NETs enhanced metastasis by activating COX-2 through Toll-like receptor 2 (TLR2). These results were further confirmed by experiments in vivo. Dnase-1 inhibition of NETs led to a decrease of COX-2 and TLR2 in subcutaneous tumors. Furthermore, the results in mouse liver metastasis model revealed the importance of NETs and COX-2 in tumor metastasis. In conclusion, NETs promote metastasis by initiating COX-2 via TLR2 in gastric cancer, and NETs may become a new target of immunotherapy.